Unilateral Tb Epididymo-Orchitis with Scrotal Fistula- A Case Report: Pharmaceutical Sciences - Medicine - Raja, Barathi; S, Karthikeyan; Tarun Teja, P.B.; P, Sasikumar (International Journal of Life Science and Pharma Research, 2022)
Tuberculosis is one of the most common worldwide diseases that remain almost unaltered in prevalence for the past few years. Genitourinary tract tuberculosis is common, but when associated with scrotal fistula it is a rare presentation. A 50 years old male came to the hospital with the complaints of pricking pain and swelling in the left side of scrotum for the past 2 months. He had history of smoking for past 40 years, on examination swelling of size approximately 6x5 cm present in left side of scrotum, globular in shape; penis pushed to right side was present, lower part of the swelling was firm to hard in consistency, left cord thickness was present and fixity to skin was also present. There was a small fistulous opening present in the left side of scrotum with no active discharge. Bilateral inguinal lymph nodes were palpable. This is a rare case presentation of tuberculous epididymo-orchitis with scrotal fistula leading to testis removal. Initially emperical treatment was started for TB epididymoorchitis which turned unresponsive, so he was then proceeded for surgery to avoid further disease progression. This case was managed radiologically, clinically and pathologically. This case report shows how the case was managed and followed up.Since symptoms of TB epididymo-orchitis are milder when compared to the symptoms of pyogenic epididymo-orchitis, they appear to physicians in later advanced stages. Tuberculosis should be considered in Patients with mild symptoms of epididymo-orchitis, mainly in those with HIV, immunosuppressive conditions and endemic areas.